2021
DOI: 10.3390/jrfm14040176
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Audit Committee Quality on the Financial Performance of Conventional and Islamic Banks

Abstract: A lot of previous research studied the relationship between audit committee quality and the financial performance of conventional banks before and during the subprime crisis, whereas some other investigations analyzed the same association in the framework of Islamic banks. However, no study has compared these two correlations either before, during, or after the subprime crisis. Several reasons explain the differences, such as the audit committee quality of each bank type, the evaluation method of the financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 74 publications
2
3
0
4
Order By: Relevance
“…Thus, this finding is coherent with Aslam and Haron (2020b). Also, it is like for the conventional banks where Haddad et al (2021) concluded that the correlation between the conventional banks' ROA and AC is statistically significant. But the AC has a significantly negative impact on ROE.…”
Section: Regression Analysissupporting
confidence: 70%
“…Thus, this finding is coherent with Aslam and Haron (2020b). Also, it is like for the conventional banks where Haddad et al (2021) concluded that the correlation between the conventional banks' ROA and AC is statistically significant. But the AC has a significantly negative impact on ROE.…”
Section: Regression Analysissupporting
confidence: 70%
“…It can be mentioned that the internal information environment does not improve the financial reporting quality. The results in the study are consistent with those reported by Abbaszadeh et al (2013), Alzeban and Sawan (2015), and Haddad et al (2021).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, as the audit committee evolves, academic research seeks to understand the usefulness of the characteristics of the audit committee, emphasising whether these characteristics affect audit quality and quality of financial reporting (Haddad et al 2021;Harris and Williams 2020;Zulfikar et al 2020). Many of these investigations have increased due to the emergence of regulatory provisions (Thansi 2004).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Pembentukan AC akan membuat penerapan GCG menjadi efektif dan efisien (Haddad et al, 2021;Setyawati & Bernawati, 2020) karena memberikan perlindungan atas kepentingan pemegang saham (McLaughlin et al, 2021) melalui fungsi pengawasan dalam memastikan setiap pelaporan keuangan yang dibuat telah sesuai dengan standar (Sari et al, 2020) sehingga kinerja perusahaan juga akan mengalami peningkatan. Pendapat lain mengatakan bahwa, untuk meningkatkan kinerja pada sebuah bank dan perusahaan sangatlah penting untuk memperhatikan atribut-atribut maupun karakteristik yang terdapat dalam AC (Manossoh, 2016).…”
Section: Pendahuluanunclassified